A Few Remarks on Sustainable Development of the Education Sphere. Postulated and Factual Improving of Education - Sztumski, Wieslaw (Problemy Ekorozwoju, 2024)
The article contains the author’s remarks about the sustainable development of the sphere of education e in our country and in similar ones. The starting point is the Agenda 2030, in which the postulate of improving the quality of education and the goals to achieve it were formulated. The author focuses on the alliance between sustainable development and education, which on the one hand consists in teaching more than before about the sustainable development, and on the other hand, on the use of education to promote the idea of sustainable development. Comparison of the postulated state of the sphere of education with the factual state leads to the conclusion of a large and growing discrepancy between them. In addition, the implementation of these postulates encounters more and more difficulties in the present. In the ever more endangered world by natural phenomenon and by military conflicts, one has first to care for survival and not for the condition of education.